STUDI LITERATUR REVIEW IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB MELALUI KEGIATAN KEPRAMUKAAN - Abdilah, Mu`ti; Maulida Aulia Rahman; Romdon, Mohammad Romdon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline in students’ discipline and responsibility has become a major challenge in the implementation of character education in Indonesia. Issues such as tardiness, violations of school regulations, lack of commitment to academic tasks, and low social responsibility highlight the need for effective and sustainable educational strategies. Scouting activities, as a compulsory extracurricular program in schools, are considered to have significant potential in character building through experiential learning approaches and the patrol system. This study aims to analyze and synthesize empirical findings related to the implementation of discipline and responsibility character education through scouting activities. The research employed a Literature Review (LR) method by examining ten national scientific articles published between 2023 and 2026, retrieved from Google Scholar and indexed national journal portals. The selection process involved identification, screening, and content analysis based on research relevance. The findings indicate that scouting activities effectively instill discipline through structured routines, rule enforcement, reward and consequence systems, and marching exercises. Responsibility is developed through role distribution within patrol groups, collaborative task completion, and camping activities that foster independence and teamwork. The success of implementation is influenced by the consistency of scout leaders, institutional policy support, and the integration of the Scout Promise (Tri Satya) and Scout Law (Dasa Dharma) values in all activities. Therefore, scouting activities are proven to be an effective and sustainable strategy for strengthening students’ discipline and responsibility character development.